Penyuluhan Pentingnya Pendidikan Bagi Anak di Dusun Sawahlega, Desa Pabuaran, Kecamatan Kemang, Kabupaten Bogor - Siti Faridah, Eva; Dahlan, Zaeni; Muttaqien, Mustika Dewi (Mitra Akademia: Jurnal Pengabdian Masyarakat, 2023)
Education is very important for children since they will be responsible for the progress of the nation and the country. However, in reality, many children still drop out of school, especially in Bogor Regency. The Dinas Pendidikan Kabupaten Bogor (Bogor Regency Education Office) noted that throughout 2021, a total of 1,884 children had dropped out of school. Responding to this fact, it is necessary to hold community outreach activities on the campaign of mainstreaming education for children in society. Based on the background mentioned above, the Islamic Religious Education and Early Childhood Islamic Education Study Program STAI Al-Hamidiyah Jakarta held community service activities in the form of counseling with the theme "The Importance of Education for Children" in Sawahlega Hamlet, Pabuaran Village, Kemang District, Bogor Regency of West Java. This community service is carried out by observing, interviewing, and preparing for the counseling activities. These community outreach activities result in some hopes that education can encourage parents and people of Dusun Sawahlega to fulfill and pay attention to the need for good education for their children.   Begitu pentingnya pendidikan bagi anak sebagai generasi penerus bangsa untuk kemajuan suatu bangsa dan negara, akan tetapi kenyataannya banyak anak putus sekolah khususnya di Kabupaten Bogor. Dinas Pendidikan (Disdik) Kabupaten Bogor mencatat sepanjang 2021, sebanyak 1.884 anak-anak putus sekolah. Melihat kondisi tersebut, maka perlu diadakan kegiatan penyuluhan pentingnya pendidikan bagi anak terhadap masyarakat. Program Studi Pendidikan Agama Islam dan Pendidikan Islam Anak Usia Dini, STAI Al-Hamidiyah Jakarta mengadakan kegiatan pengabdian kepada masyarakat dalam bentuk penyuluhan di Dusun Sawahlega, Kecamatan Kemang, Kabupaten Bogor. Diharapkan dengan dilaksanakannya kegiatan penyuluhan tentang pendidikan dapat mendorong peran orang tua dan masyarakat Dusun Sawahlega dalam memenuhi dan memberikan perhatian kebutuhan pendidikan yang baik terhadap anak-anaknya sebagai generasi bangsa.